FROM PYRENEES LATIN TO HISPANIC ROMANCE: HISTORICAL, CULTURAL AND LINGUISTIC ASPECTS - Korbozerova , Nina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with the social, cultural and linguistic features of the evolution of the Spanish language from the 2nd century BC to the 8th century AD, which corresponds to the period of development and formation of Iberian, or Pyrenees, Latin (200 BC – 409 AD) and to the period of formation and development of primitive Spanish language (409 – 711 AD).The distribution of these two periods of development of the Spanish language corresponds to historical, social and cultural factors, correlated chronologically to two periods of conquest of the Iberian peninsula – Roman and German, which differ in their historical, national, cultural and linguistic consequences. As a result of the Roman conquest, the people inhabiting the Iberian peninsula were completely romanized by adopting the more developed social institutions, a high culture and a better language of the Romans, which became in the future the basis of the Spanish language.German tribes as conquerors of the Iberian peninsula were romanized, having adopted the Spanish way of life. However, in this article, the author suggests a hypothesis of the existence of a significant influence of the German superstar than the borrowing of a small number of words. This influence is also observed at the phonological level. As a result, in the 6th century in the Spanish language took place a large-scale consonant shift and a significant phonological changes.The results of the study confirm that in the Roman Empire since 200 BC there were different forms of vulgar Latin, in particular Spanish Latin, and between 500 and 600 AD there are preconditions for the emergence of Roman languages, in particular the primitive Spanish language, which is called in this article as HISPANIC ROMANCE, or ROMANCE HISPÁNICO.____________References• Alisova, T. B., Repina, T. A., Tariverdieva, M. A. Vvedenie v romanskuju filologiju (Moskva, 1987).• Grigor'ev, V. P. Istorija ispanskogo jazyka (Moskva, 1985).• Korbozerova N. Historia de la lengua española (Kyiv, KNU, 2015).• Rodríguez, Rosique S. La época visigoda, www.cervantesvirtual.com /...visigoda…/00f492.12-82b2-11d...• 5. Lapesa, Rafael. Historia de la lengua española (Madrid, 1981).• 6. Litvinenko, E. Historia de la lengua española. – K., 1983.• Los Escipiones, una saga que cambió el runbo de España, http://www.nationalgeograrhic.com.es/ …/• 8. Masluchenko, N. Antología de la lengua española (, 1976).• 9. Menéndez Pidal, Ramón. Orígenes del español (Madrid, Espasa-Calpe, 1980).• Segunda Guerra Púnica. Escipión contra Aníbal, historia-roma.com/
Keywords: Pyrenees Latin, primitive Spanish language, historical aspect cultural aspect, linguistic aspect, German superstar